Особливості перезимівлі деревних витких рослин дендрологічного парку “Олександрія” НАН України - Doiko, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
The results of study of influence of low temperatures of winter periods 1998–1999 and 1999–2000 on hibernating 14 species of ligneous lianes, which introdused in the dendrological park Alexandria of the NAS of Ukraine. The brief description of damages of low temperatures of yearly shoots are gave. The influence on introdused plants of late spring frosts was marked.